An empirical evaluation of learner performance in e-learning recommender systems and an adaptive hypermedia system - Ghauth, K.I.; Abdullah, N.A. (2010)
This paper introduces a novel architecture for an e-learning recommender system which is based on good learners' average ratings strategy and content-based filtering approach. The feasibility of the proposed system is conducted by comparing its performance against other recommender systems and an adaptive hypermedia system in order to measure the effectiveness of the proposed strategy in improving students' learning performance. Experimental result has shown that the recommender strategy can improve students' performance by at least 12.16, as compared to other recommendation techniques. A performance evaluation with an adaptive hypermedia system that uses knowledge level as its adaptation feature also showed a positive increase of 14.99 in terms of students' performance.